2019
DOI: 10.1111/cen.14117
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular risk profile of middle‐aged women with polycystic ovary syndrome

Abstract: ObjectivesContradictory results have been reported regarding the association between polycystic ovary syndrome (PCOS) and cardiovascular disease (CVD). We assessed the cardiometabolic phenotype and prevalence of CVD in middle‐aged women with PCOS, compared with age‐matched controls from the general population, and estimated 10‐year CVD risk and cardiovascular health score.DesignA cross‐sectional study.Participants200 women aged >45 with PCOS, and 200 age‐matched controls.MeasurementsAnthropometrics, insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 40 publications
2
23
1
3
Order By: Relevance
“…Several cardiovascular risk factors associated with PCOS seem to ameliorate over time. 224 In a meta-analysis performed for the development of the ESHRE/American Society for Reproductive Medicine guidelines on PCOS, and restricted to only higher quality studies, no increased risk of MI, stroke or CAD was found in women with PCOS compared to controls. 225–227 Another meta-analysis confirmed that the risk of CVD was increased in women of reproductive age, but not in peri- or post-menopausal women.…”
Section: Hormonal Dysregulation and Cardiovascular Disease Riskmentioning
confidence: 99%
“…Several cardiovascular risk factors associated with PCOS seem to ameliorate over time. 224 In a meta-analysis performed for the development of the ESHRE/American Society for Reproductive Medicine guidelines on PCOS, and restricted to only higher quality studies, no increased risk of MI, stroke or CAD was found in women with PCOS compared to controls. 225–227 Another meta-analysis confirmed that the risk of CVD was increased in women of reproductive age, but not in peri- or post-menopausal women.…”
Section: Hormonal Dysregulation and Cardiovascular Disease Riskmentioning
confidence: 99%
“…Hyperandrogenaemia has been associated with adverse health consequences in young women 14 . However, Meun et al have reported that the prevalences of dyslipidaemia, insulin resistance, type 2 diabetes, metabolic syndrome, evidence of atherosclerosis and cardiovascular disease do not appear to differ between women at midlife with a prior diagnosis of polycystic ovary syndrome (PCOS) than age‐matched controls, despite BMI, systolic blood pressure and androgen concentrations being higher in the women with prior PCOS 15 . An important question is whether the restoration of T concentrations in older women to concentrations seen in premenopausal women, along with the increase in T over 3 years observed in over 50% of the women aged 70–79 years from baseline offers any survival advantage.…”
Section: Discussionmentioning
confidence: 99%
“…The Study of Women’s Health Across the Nation (SWAN) study indicated no association between a history of HA or menstrual irregularity and impairment of metabolic condition after menopause ( 33 ). Meun et al ( 28 ) did not observe significant difference in the prevalence of MS between women with PCOS and controls at the age of 50. Overall, women with PCOS experience a higher risk of MS during the reproductive period.…”
Section: Metabolic Syndromementioning
confidence: 92%
“…Although several studies and meta-analyses showed a higher prevalence of overweight and obesity in women with PCOS than in women without PCOS, the data in aging women with PCOS are insufficient ( 9 , 27 ). Meun et al ( 28 ) recently observed higher body mass index (BMI) values and increased waist circumferences in women with PCOS aged >45 years than in healthy controls. Wild et al ( 29 ) reported significantly higher BMI and waist-to-hip ratio (WHR) values in a PCOS group than in a control group in a 31-year follow-up study.…”
Section: Obesitymentioning
confidence: 99%